PENENTUAN ELEKTROMOTANSI TERMAL BEBERAPA JENIS TERMOKOPEL DENGAN PASANGAN LOGAM YANG BERVARIASI - Karim, Saeful; Sunardi, Sunardi (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2006)
An experiment has been done to observe about relation of difference temperature with electromotive force between two metal junctions. This experiment directed to determine the coeficient thermal electromotantion from some termocouples and to find metal junction which most linier. In this experiment used experimental method with some instrument, there is thermometer, galvanometer, and potentiometer ( nichrom ). Termocouple is used in this experiment bent two metal junction, there is cooper – steel, nichrom-steel, nichrom – cooper, irom-steel, iron-nichrom, and cooper – iron. Extending of temperature is used inthis experiment there is reference temperature ( To = 1 oC ) and measuring temperature ( 30 – 75 oC ). From this experiment we find some illustrations that the more higher of difference temperature between two metal junction there for the more higher too of electromotive force has producted from two metal junctions ( termocouple ). For junction cooper iron and iron nichrom has producted non linier relation ( relation of electromotive force with difference temperature ). But for junction cooper steel, nichrom steel, and iron steel has producted linier relations, junction nichrom cooper have relation most linier with coeficient thermal electromotantion 0,0472 mV/ 0C.Coeficient thermal electromotantion will be different depend on metal.